Construction of Chiral Nanoassemblies Based on Host-Guest Complexes and Their Responsive CD and CPL Properties: Chirality Transfer From 2,6-helic[6]arenes to a Stilbazolium Derivative - Guo, Yan; Han, Ying; Chen, Chuan-Feng (Frontiers in Chemistry, 2019)
A couple of water-soluble chiral 2,6-helic[6]arene derivatives P-H1 and M-H1 were synthesized, and they could form 1:1 stable complexes with 4-[(4'-N,N-diphenylamino)-styryl]-N-methylpyridinium iodide (G) in water. Compared with G, the host-guest complexes exhibited enhanced fluorescence, which might be attributed to the spatial confinement of G and restriction of aggregation-caused quenching (ACQ) effects. Based on the host-guest complexation, the first helic[6]arene-based chiral assemblies were then constructed, and they showed rectangular or hexagonal nanostructures by scanning electron microscopy (SEM) images. Interestingly, the assemblies showed clear mirror-image circular dichroism (CD) and circularly polarized luminescence (CPL) spectra in aqueous solution, revealing a consecutive chirality transfer from the chiral macrocyclic cavities of the hosts to G. Moreover, the supramolecular chirality of the assemblies could also show responsiveness to the pH values and temperatures of the system.